Assessment of the Effect of High Tide and Low Tide Condition on Stream Flow Velocity at Sungai Rompin's Mouth. Issue 1 (September 2020) - Akhtar, M N; Anees, M T; Bakar, E A
Abstract: The variation in stream flow velocities depends on the riverbed slopes. In upstream areas, where slope is steep, the magnitude of velocity is high, whereas in downstream areas, where slope is gentle, the magnitude of velocity is slow. The focus of this study is in the downstream area, where variations in the magnitude of velocities are due to high tide and low tide situations. Due to sea level rise, flooding occurs with high tides in several coastal regions which causes road closures due to submerged in water and public inconveniences. Velocities in high tide conditions need to be examine for safety and health risk of people. Therefore, the main objective of this study to assess the variation in velocity values of stream flow at both high tide and low tide condition near river mouth. One dimensional Hydrological Engineering Centre-River Analysis System (HEC RAS) simulation was conducted 9.4 km along reach of Sungai Rompin. A total of 188 river cross sections were used at an interval of 50 m. Other river geometries such as river central line, riverbanks and flow paths were constructed in RAS mapper of HEC RAS. The unsteady flow was run in both high tide and low tide conditions. The outputs of the simulation were compared and analysed. The results revealed that the stream flow velocities reduced up to 60% in high tide condition when compared to the low tide condition near the river mouth.